Розробка автоматизованої системи моніторингу та діагностування технічного стану електродвигунів - Шафоростов, Д. Д. (ХНУРЕ, 2021)
Electric vehicles are currently receiving a lot of attention, they are more environmentally friendly and do not pollute the environment. But in order to avoid sudden breakdowns, their parts must be monitored. The engine has a great influence on the operation of electric transport. It will be more reliable and inexpensive to use an engine monitoring system than to undergo regular inspections. Therefore, a very important measure is to monitor the current state of asynchronous motors using information technology to prevent accidents and their complete failure
Keywords: електродвигуни; автоматизована система моніторингу; технічний стан; діагностування